Kerjasama Indonesia - Malaysia dalam Peningkatan Taraf Pendidikan Anak TKI di Negeri Sabah - Anita; Darwis; Aswin Baharuddin (Hasanuddin Journal of International Affairs, 2021)
This study aims to describe the effectiveness and challenges of Indonesia- Malaysia cooperation in improving the education level of the Indonesian labour’s Children in Sabah, Malaysia. The research method used in the preparation of this thesis is a descriptive qualitative method which aims to describe the effectiveness and challenges of Indonesia-Malaysia cooperation. The data collection technique used is a literature review that comes from various literatures such as books, journals, documents, articles, and electronic media such as the internet. In this research, the writer also uses qualitative data analysis with deductive writing method. The results of this study indicate that there is a good relationship that exists between Indonesia and Malaysia through bilateral cooperation between the two countries in solving the problems of children of Indonesian labour workers residing in the country of Sabah. Indonesia implements the foreign policy with the aim of achieving its national interest, namely intellectual life of the nation. In its implementation, accompanied by the issuance of the Guidelines for Establishing CLC in Sabah by the Malaysian Ministry of Education, Indonesia has implemented several policies to facilitate the provision of educational services to the children of Indonesian migrant workers. These include establishing the Sekolah Indonesia Kota Kinabalu (SIKK), the establishment of a Community Learning Center (CLC), the implementation of sending Indonesian teachers to Sabah next repatriation programs, as well as the issuance of official documents or population documents, namely passports, birth certificates, and marriage certificates. The collaboration between Indonesia and Malaysia can be said to be quite effective, as seen from the increase number of teachers accompanied by the addition of available education levels, namely CLC SD and CLC SMP which are widely spread and are directly proportional to the increase Indonesian labour’s children who can access education/get educational services. Penelitian ini bertujuan untuk mendeskripsikan efektivitas dan tantangan dari kerjasama Indonesia-Malaysia dalam peningkatan taraf pendidikan anak-anak TKI yang ada di Negeri Sabah, Malaysia. Metode penelitian yang digunakan dalam penyusunan skripsi ini adalah metode kualitatif deskripstif yang bertujuan untuk mendeskripsikan efektivitas dan tantangan dari kerjasama Indonesia- Malaysia. Teknik pengumpulan data yang digunakan adalah telaah pustaka yang bersumber dari berbagai literatur seperti buku, jurnal, dokumen, artikel, maupun media elektronik seperti internet. Dalam penelitian ini, penulis juga menggunakan analisis data kualitatif dengan metode penulisan deduktif. Hasil penelitian ini menunjukkan adanya hubungan baik yang terjalin antara Indonesia dan Malaysia melalui kerjasama bilateral kedua negara dalam menyelesaikan permasalahan anak TKI yang berada di negeri Sabah. Indonesia mengimplementasikan kebijakan luar negerinya dengan tujuan untuk mencapai kepentingan nasionalnya, yaitu mencerdaskan kehidupan bangsa. Dalam penjalanannya, disertai dengan dikeluarkannya Pedoman Penubuhan CLC di negeri Sabah oleh Kementerian Pelajaran Malaysia, Indonesia menjalankan beberapa kebijakan untuk memudahkan pemberian layanan pendidikan kepada anak-anak TKI. Diantaranya mendirikan Sekolah Indonesia Kota Kinabalu (SIKK), terbentuknya Community Learning Center (CLC), pelaksanaan pengiriman guru Indonesia ke Sabah hingga program repatriasi, serta penerbitan dokumen resmi atau dokumen kependudukan, yakni berupa Paspor, Surat Akta Kelahiran, dan Surat Pernikahan. Kerjasama yang dilakukan antara Indonesia dan Malaysia dapat dikatakan cukup efektif dilihat dari adanya penambahan jumlah guru disertai penambahan jenjang pendidikan yang tersedia yaitu CLC SD serta CLC tingkat SMP yang banyak tersebar dan berbanding lurus dengan bertambahnya anak-anak TKI yang dapat mengakses pendidikan/mendapatkan layanan pendidikan.